Assessment of chemical compositions in coral skeletons (Acropora digitifera and Porites australiensis) as temperature proxies - Sakata, Shoko; Inoue, Mayuri; Tanaka, Yasuaki; Nakamura, Takashi; Sakai, Kazuhiko; Ikehara, Minoru; Suzuki, Atsushi (Frontiers in Marine Science, 2024)
Although biogenic carbonates, such as foraminifera and coccolithophorids, are valuable tools for reconstructing past environments, scleractinian corals also offer environmental data from tropical to subtropical regions with a higher time resolution. For example, oxygen isotopes (δ 18 O) and strontium-calcium (Sr/Ca) ratios have been utilized to reconstruct sea surface temperatures and salinity, primarily through the use of massive-type Porites sp. from the Pacific, as well as corals like Diploria and Montastrea from the Atlantic. While a few types of corals other than Porites have been utilized in paleoclimate studies, comprehensive evaluations of their geochemical tracers as temperature proxies have not been thoroughly conducted. Therefore, in this study, we focused on branching-type Acropora, which are found worldwide and are often present in fossil corals. We conducted a comparison of the chemical compositions (δ 18 O, δ 13 C, Sr/Ca, U/Ca, Mg/Ca, and Ba/Ca) of Acropora digitifera and Porites australiensis through temperature-controlled culture experiments.